2002
DOI: 10.1021/jf011298v
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Enzymatic Method To Quantify Methyl Ketones from Bacterial Origin

Abstract: Methyl ketones are detected in dry fermented sausages in which they contribute to the cured aroma. They have been associated with the inoculation of Staphylococcus carnosus used as starter culture. To evaluate the ability of bacterial starters to produce methyl ketones it was necessary to develop a rapid method. The method consists of a reaction catalyzed by a commercial NADPH-dependent alcohol dehydrogenase that reduces the 2-pentanone to its secondary alcohol. The linearity, the specificity, and the robustne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The procedure employs a thermostable NADPH-dependent alcohol dehydrogenase (ADH) (EC 1.1.1.2) [16]. This enzyme reduces the methyl ketone to its secondary alcohol and the rate of NADPH oxidation is directly related to the ketone content [17]. The enzymic reduction of 2-pentanone was monitored continuously with a Shimadzu UV-Visible 160A spectrophotometer.…”
Section: Enzymic Methods To Quantify Methyl Ketonesmentioning
confidence: 99%
“…The procedure employs a thermostable NADPH-dependent alcohol dehydrogenase (ADH) (EC 1.1.1.2) [16]. This enzyme reduces the methyl ketone to its secondary alcohol and the rate of NADPH oxidation is directly related to the ketone content [17]. The enzymic reduction of 2-pentanone was monitored continuously with a Shimadzu UV-Visible 160A spectrophotometer.…”
Section: Enzymic Methods To Quantify Methyl Ketonesmentioning
confidence: 99%
“…Concerning S. carnosus , Engelvin et al [3] have reported the existence of a β‐oxidative pathway and the liberation of intermediates from a β‐oxidation cycle. Recently, we have reported a β‐decarboxylase activity in resting cells of S. carnosus using a β‐ketoacid as substrate [4,5]. These results show that S. carnosus , as do fungi, may produce ketones via this pathway.…”
Section: Introductionmentioning
confidence: 68%
“…The reduction of ketones by the ADH was monitored spectrophotometrically with a Shimadzu ultraviolet (UV)‐visible 160A spectrophotometer in kinetic mode [4]. The reaction mixture, in Tris–HCl buffer (100 mM, pH 7.8) and made up to a final volume of 1 ml, contained the following reagents: 200 μl of sample, 50 μl of β‐NADPH (4 mM), 21 μl of ADH solution (0.94 U ml −1 ).…”
Section: Methodsmentioning
confidence: 99%
“…In bacteria, methylketones, such as 2-heptanone, 2-butanone, 2-petanone, and 3-methyl-1-butanone, are detected in the volatile organic compounds (VOCs) of Lactobacillus casei (Gallegos et al, 2017). Staphylococcus carnosus produces 2-pentanone and a highly autolytic strain of Lactobacillus helveticus is reported to enhance the levels of methylketones during cheese ripening (Fadda et al, 2002; Hannon et al, 2006). In fungi, both 2-heptanone and 2-petanone are detected from a range of species, from unicellular yeast to filamentous fungi (Sunesson et al, 1996).…”
Section: Introductionmentioning
confidence: 99%